The podocyte: glomerular sentinel at the crossroads of innate and adaptive immunity - Burke, George W.; Mitrofanova, Alla; Fontanella, Antonio; Ciancio, Gaetano; Roth, David; Ruiz, Phil; Abitbol, Carolyn; Chandar, Jayanthi; Merscher, Sandra; Fornoni, Alessia (Frontiers in Immunology, 2023)
Legend has it that Blues guitarist extraordinaire Robert Johnson sold his soul to the devil in return for being taught how to play the guitar. The deal was consummated at the crossroads of Highway 49 (known as the Blues Highway) and Route 61 in Clarksdale, Mississippi in 1927. Robert Johnson went on to become the father of American blues music, The King of the Delta Blues, spawning a generation and genre of African-American Blues musicians.It remains to be determined whether the podocyte in being positioned also at the crossroads of innate and adaptive immunity, was by divine intervention, or perhaps a deal made with the devil, similar